Optimal Capital Structure of Public-Private Joint Ventures - Gasiorowski, Pawel (IMF Working Papers; Working Paper ;, 2008)
This paper presents a model to assess the efficiency of the capital structure in public-private partnerships (PPP). A main argument supporting the PPP approach for investment projects is the transfer of know-how from the private partner to the public entity. The paper shows how different knowledge transfer schemes determine an optimal shareholding structure of the PPP. Under the assumption of lower capital cost of the public partner and lower development outlays when the investment is carried out by a private investor, an optimal capital structure is achieved with both the public and the private parties as shareholders.